Deportation of Latvian citizens on the 25th of March in 1949. Structural analysis. - Skinke, Iveta (Genocidas ir rezistencija, 2008)
Based on documented statistics, this is an overview of the largest deportation of Latvian citizens in March 1949. This overview provides a comprehensive and concentrated look at the deportations, their course and their impact on Latvian society. The main data used for the structural analysis on the Latvian population deported on 25 March 1949 are taken from the Latvian State Archives database, which consists of 13,283 archive files of Latvian citizens.